Mediated Catholic Mass During the COVID-19 Pandemic: On Communication, Technology and Spiritual Experience - Tonggo, Hasian Laurentius; Irwansyah, Irwansyah (Jurnal Komunikasi, 2021)
The COVID-19 pandemic has prompted Catholic churches in Indonesia to conduct physical distancing, close their doors and move mass to online media or television. This situation is something extraordinary for the Catholic church which is known to adhere to tradition in the implementation of its worship. This study aims to determine the experience of Catholics in conducting mediated worship using Religious-Social Shaping of Technology examining and concepts, namely social affordance, religion-online/online-religion, and digital media law. This qualitative research is done by interviewing six informants using descriptive phenomenological approach. The results of the study indicate four main findings. First, informants have the freedom to choose the tools or channels to attend the mediated mass. Second, the interactivity in the mediated mass is lost. Third, the atmosphere of the mediated mass can have an impact on the solemnity of worship. Fourth, the use of technology for mediated mass cannot absolutely be paralleled with physical worship, but some informants still hope that the mediated mass will be held after this pandemic. This research concludes that mediated mass during a pandemic is not as ideal as a physical mass because the experience gained is not optimal, but it opens up wider opportunities to reach people who may not be physically present in church from anywhere. Academically, this research is expected to increase the wealth of knowledge about mediated worship during a pandemic. Meanwhile, in practical terms, this research can be a reference for the church to improve its overall quality. Pandemi COVID-19 membuat gereja Katolik di Indonesia melakukan physical distancing bahkan menutup pintunya dan mengalihkan misa ke media daring atau televisi. Keadaan ini merupakan sesuatu yang luar biasa bagi gereja Katolik yang terkenal memegang teguh tradisi dalam pelaksanaan ibadahnya. Penelitian ini memiliki tujuan yaitu ingin mengetahui pengalaman umat Katolik dalam melakukan ibadah termediasi dengan menggunakan Religious-Social Shaping of Technology serta beberapa konsep lain, yaitu social affordance, religion-online/online-religion, dan hukum media digital. Adapun pelaksanaan penelitian kualitatif ini adalah dengan mewawancarai enam informan menggunakan pendekatan fenomenologi deskriptif. Hasil penelitian ini menunjukkan empat temuan utama. Pertama, informan memiliki kebebasan untuk memilih alat maupun kanal untuk mengikuti misa termediasi. Kedua, interaktivitas dalam misa termediasi menjadi hilang. Ketiga, suasana misa termediasi bisa berdampak pada kekhusyukan saat beribadah. Keempat, pemanfaatan teknologi untuk misa termediasi memang tidak bisa mutlak disejajarkan dengan ibadah fisik namun sebagian informan tetap mengharapkan misa termediasi dilakukan setelah masa pandemi ini. Penelitian ini menyimpulkan bahwa misa termediasi selama pandemi memang tidak seideal misa fisik karena pengalaman yang diraih tidaklah maksimal, namun membuka peluang lebih luas untuk menjangkau orang-orang yang tidak mungkin hadir secara fisik di gereja dari mana saja.Secara akademis penelitian ini diharapakan dapat meningkatkan khazanah pengetahuan tentang ibadah termediasi pada saat pandemi. Sementara secara praktis, penelitian ini dapat menjadi acuan bagi gereja untuk meningkatkan kualitas secara menyeluruh.